2020
DOI: 10.3389/fchem.2020.582490
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Specific Functionalisation of Carbon Fibers for Advanced Flexible Biosensors

Abstract: This review aims at offering an up-to-date comprehensive summary of carbon fibers (CFs)-based composites, with the emphasis on smart assembly and purpose-driven specific functionalization for their critical applications associated with flexible sensors. We first give a brief introduction to CFs as a versatile building block for preparation of mutil-fountional materials and the current status of research studies on CFs. This is followed by addressing some crucial methods of preparation of CFs. We then summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…[198], Copyright 2016, John Wiley and Sons good biocompatibility, simple manufacturing process, and low cost of CFs are desirable properties for manufacturing implantable devices and developing practical applications. CF-based biosensors are widely used to monitor human physiological indices and cellular active components [205]. Charles et al [206] proposed that to avoid tissue damage after inserting traditional enzyme biosensors with a platinum electrode into the brain, the large platinum electrode could be replaced with platinum-plated CF microelectrodes.…”
Section: Implantable Biosensorsmentioning
confidence: 99%
“…[198], Copyright 2016, John Wiley and Sons good biocompatibility, simple manufacturing process, and low cost of CFs are desirable properties for manufacturing implantable devices and developing practical applications. CF-based biosensors are widely used to monitor human physiological indices and cellular active components [205]. Charles et al [206] proposed that to avoid tissue damage after inserting traditional enzyme biosensors with a platinum electrode into the brain, the large platinum electrode could be replaced with platinum-plated CF microelectrodes.…”
Section: Implantable Biosensorsmentioning
confidence: 99%
“…Carbon fibers (CFs) contain more than 90 wt.% of carbon and exhibit many outstanding properties such as high modulus (200–900 GPa), high compressive strength (up to 3 GPa), high tensile strength (2–7 GPa) [ 1 , 2 ], flexibility and tunable electrochemical performance. Therefore, they can be used in multiple fields of applications [ 3 ], such as aerospace, automobile, the chemical industry, transportation, construction, energy storage, sewage treatment and others [ 4 ]. The first step of a CF production process is to select the precursor material that determines the properties and applications of CF produced from it [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been commonly used as a gas and humidity sensors for: LPG gas [11], ammonia [12], SO 2 [13], ethanol [14,15], acetone [16,17], humidity [18] and other applications, such as photocatalysts [19,20], solar cells [21,22], etc. Due to their various physical and chemical properties, carbon compounds in their different morphological forms such as fibre [23], nanotube (CNT) [24], and graphene [25], have been widely studied for their potential application in sensors as materials for reinforcing and improving the detection properties of sensitive layers based on semiconductor oxides [26][27][28]. For instance, Kaur et al [29] reported that the addition of reduced graphene oxide (rGO) to Gd-doped WO 3 led to a significant increase in acetone response with a reduction in the optimum operating temperature and improved selectivity.…”
Section: Introductionmentioning
confidence: 99%